Failure mechanism and bearing capacity of cold-formed steel trusses with HRC connectors. (15th December 2019) - Mathieson, Chris; Roy, Krishanu; Charles Clifton, G.; Ahmadi, Amin; Lim, James B.P.
Highlights: Four-point bending, and cyclic tests were conducted on 26 specimens of CFS trusses with different type of connections. Howick Rivet Connector (HRC) outperformed the strength of traditional truss connections. The effects of number of HRCs, screws, bolts and washers were also tested in the experimental investigation. Test results were compared against the AISI & AS/NZS design strengths. A proposed modification to the design equation is offered for calculating the shear capacity of CFS trusses with HRC connectors. Abstract: Portal frame structures, made up of cold-formed steel (CFS) trusses, are increasingly being used for lightweight building construction. There are different types of connectors available to assemble CFS trusses, which include CFS self-drilling screws, bolts and nails. Recently, a novel pin-jointed connector, called the Howick Rivet Connector (HRC), was developed and tested in T-joints to determine its reliable strength, stiffness and moment resisting capacity. The results from T-joint testing provided a background to the performance and reliable capacity of the HRC in shear. This paper focuses on the application of the HRC in a truss configuration. Four-point loading and cyclic tests were conducted on 26 specimens, which include two different thicknesses and two different cross-sections of channel sections to make the truss assembly. The HRC was used to provide a pinned connection between CFS channel sections through their flanges. The effects of number of HRCs, screws, bolts and washers were also tested in the experimental investigation. Both concentric and eccentric loadings were applied. All HRCs used in the trusses were 12.7 × 0.95 mm because of the availability of this tube size; except for trusses with 90 × 40 mm members connected with Tek screws. Interactions between the connection and connecting elements were examined closely. The main failure mechanisms for the trusses were bearing and rivet shear of the critical connections and buckling of the compression web member due to concentrated actions. The tests with 0.75 mm thick members failed in bearing unless washers were provided; in which case, they failed in rivet shear. However, for 0.95 mm thick members, the shear failure of rivet was observed, unless bolts were inserted; here, bearing failure occurred.